058 The interactions of Sleep, Heart Rate Variability and Aging on an Emotional Directed Forgetting Memory Task. (3rd May 2021) - Sattari, Negin; Upadhya, Anisha; Vinces, Karla; Mednick, Sara
Abstract: Introduction: The ability to forget information plays an important role in our daily lives. Sleep plays a role in memory formation and as we age, sleep-quality and memory decrease. For emotional memory a drop in preference for negative stimuli is presented with aging. Heart-rate variability (HRV), a measurement of cardiac autonomic-activity, has been related to cognitive processes. It is unknown how HRV impacts sleep-dependent memory updates in older adults. Here, we investigated HRV and sleep-related emotional memory updates in the context of aging using a Directed-Forgetting (DF) paradigm. Methods: We tested younger [N=105, 18-25yr] and older adults [N=119, 60-85yr]. Subjects encoded a DF Word-Paired task, in which either negatively/neutrally-valenced word-pairs were cued to-be-remembered (Retain) or forgotten (Alter) for a later test. They then took a polysomnographically-recorded (PSG) nap including HRV. Next, recognition was tested. Memory for both Retain and Alter words was measured. We compared memory, sleep-quality measured by Sleep-Efficiency (SE) and HRV, measured by normalized High-Frequency (HFnu), an indicator of parasympathetic activity. Bivariate correlations were used to measure the associations. Results: Younger adults showed greater performance on both Retain and Alter word-pairs (p<.001) with being able to better forget Alter word-pairs only for the negative-condition (p<.001). Younger adults had a higher SE (p<.001) and a higher HRV-HFnu in both Stage2 (p=.02) and Stage3 (p =.03). Only for older adults in the neutral-condition, we found correlations between memory and sleep [Retain: r(20)=.52, p=.01; Alter: r(20) =.51, p=.01]. Finally, among younger adults, in Stage 2, memory was related to HFnu for both neutral [Retain: r(17) = .46, p=.05] and negative-condition [Retain: r(25) = -.41, p =.03; Alter: r(25) = -.39, p =.05]. No correlations were found for older adults(all ps>.11). Conclusion: Our result indicate a possible loss of the ability to intentionally forget irrelevant information among older adults and a role for the saliency to forget irrelevant items among younger adults. In addition, aging brain may benefit from sleep only for the neutrally-valenced items; the memory biased seen in aging. Finally, for younger adults HRV may be related to memory updates and its role depends on specific sleep stages however this association is faded away with aging. Support (if any):